Immigration to Europe between emergency and integration: The case of the "land of Fires" - Francesco Dandolo; Michele Mosca (The Journal of European Economic History, 2020)
The territories between Casal di Principe and the Domitian Coast have been at the center of the migratory dynamics that have involved Italy for several decades. The massive use of immigrants for agricultural labor and the murder of Jerry Essan Masslo are elements of a crucial chapter of the history of Italian immigration. Another is the pastoral work of Father Peppe Diana, realizing full fraternity in the encounter with immigrants and inspiring significant and extraordinarily interesting experiences of hospitality and integration in a difficult context. Models of social inclusion were developed that promoted new forms of active citizenship, transcending the logic of emergency which immigrants often face in one of the parts of Italy where organized crime is most deeply rooted. The result is an innovative approach to human relationships, rich in opportunities, which points the way to civil coexistence in an increasingly plural society; an original paradigm of civic ethics that injects much needed calm and objectivity into the debate on these issues.
Keywords: 330